DNA on drugs! A preliminary investigation of DNA deposition during the handling of illicit drug capsules. (September 2021) - Griffin, Amy; Kirkbride, K. Paul; Henry, Julianne; Painter, Ben; Linacre, Adrian
Abstract: DNA profiling from capsules and tablets offers a complementary tool to that of chemical profiling when investigating the manufacture and trade in illicit drugs. By sampling the outside of capsules, individuals who may have handled them during production, assembly or distribution may have deposited their DNA and can be identified if matched to a nominated profile or one on a relevant DNA database. The profiles can also be compared to those found on other capsules to potentially link various drug seizures. This study sampled the exterior of capsules after they had been handled in a controlled scenario to determine if informative DNA profiles could be generated from this brief contact. Two individuals of intermediate shedder status washed their hands and waited for 30 min before handling ten gelatine, vegetable, and enteric vegetable capsules each (n = 60). Contact was made for 15 s. Each capsule was swabbed and DNA isolated. The amount of recovered human DNA was quantified and profiled using the Verifiler Plus DNA profiling kit. Profiles were generated from 82% (49/60) of capsules tested with LR values above 1 × 10 3 for the inclusion of the volunteer as a contributor. Inhibition of the PCR was detected in 24 of the 60 samples, however 16 of these still produced informative profiles when sufficient template DNA was available and only mild inhibition was detected, or by overcoming inhibition by dilution of the DNA extract. This pilot study demonstrates the potential for forensic science laboratories to recover human DNA from the exterior surface of capsules which are commonly used to encase illicit drugs such as MDMA, thus enabling both biological and chemical profiling methods to contribute to the investigation of clandestine drug production and distribution. Highlights: First study obtaining DNA profiles from capsules used to contain ecstasy. Informative profiles from touch DNA were produced for 48 out of 60 capsules. Now possible to profile illicit drugs biologically as well as chemically.